Caracterização da deposição de pó cerâmico supercondutor de YBa2Cu3O7-d e SmBa2Cu3O7-d em aço inoxidável 316L - Corteletti, Rodolpho Toniato (2019)
In this work, microstructures of superconducting ceramics deposited in 316L stainless steel base were produced and characterized. The objective was to develop a fault currente limiter and evaluate the metal / ceramic junction and to change the mechanical properties of the superconducting ceramics. Thus, for this purpose in mind, YBa2Cu3O7-d and SmBa2Cu3O7-d polycrystalline ceramics were prepared by conventional method from the solid-state reaction. In addition, the 316L stainless steel plates were cut into rectangular pieces of approximately 72 mm x 10 mm x 2.5 mm. The yttrium-based superconducting ceramics deposited in the steel were named sample A and samarium-based ceramics were named sample B. Each of the samples were thermally treated with different isotherms. Sample A was maintained at a plateau of 1040 ° C and sample B at a plateau of 1060 ° C, followed by cooling to 520 ° C for 24 hours. It is then cooled to room temperature. All thermal process was under oxygen flow with 99.9% purity. The characterization of these samples was performed by X-ray diffraction, optical microscopy, scanning electron microscopy and dispersive energy spectroscopy. The results indicate that the ceramics covered steel body, there are recrystallized signals and presented a boundary size of grain outline. We conclude that the composite preparation process was effective in the control of grain boundary size.